Comparación de cambios morfológicos de papilas ruminales en terneros lactantes alimentados con probióticos en hacienda San Luis, Cotopaxi. - Sánchez Pérez, Roger Marcelo (2019)
The present study was conducted at the San Luis farm in the province of Cotopaxi, Ecuador and whose main objective was to evaluate variables for both length and width of ruminal papillae in two newborn animals, the experimental animal was feed by probiotics (lactobacillus acidophilus and Saccharomyces cerevisiae), and the witness was not. The animals were subjected to the same driving and environmental conditions, in addition they were evaluated physiological constants and blood values, in order to get ensure that both animals were in same conditions, weight measurements were made every week with the final purpouse to get zootechnical values: final weight, daily weight gain, body condition. After the sacrifice of the animals, rumen was divided into five areas of each animal, then we got 100 sampes of one cm2 of each rumen, they were observed in the laboratory of university of americas (UDLA) by an estereoscopic microscope and the measurements were made by the software of the microscope. Statistical studies of T-test for independent samples and ANOVA were applied, concluding that there is a sifnificant difference for the variable of height in rumen papillae of the animal suplemented with probiotics, it concludes that the intake of lactobacillus acidophilus and Saccharomyces cerevisiae produce morphologic changes o the heigt of the papillae and estimulates an diary increase of 56 gr. per day on the supplemented animal T1 in reference of the not supplemented T0